Independent phase modulation for quadruplex polarization channels enabled by chirality-assisted geometric-phase metasurfaces - Yueyi Yuan (Nature Portfolio, 2020)
Here the authors propose an approach to construct metasurfaces, which activate all circularly polarized channels and make full utilization of transmitted energy simultaneously. By introducing chirality-assisted phase all the components in the Jones matrix can be decoupled and independently tuned.